CFTR ion transport deficiency primes the epithelium for partial epithelial-mesenchymal transition in cystic fibrosis - Rodrigues, Cláudia S.; Canto, Matilde; Torres, Raquel; Railean, Violeta; Ramalho, Sofia S.; Farinha, Carlos M.; Pankonien, Ines; Amaral, Margarida D. (Frontiers in Pharmacology, 2025)
IntroductionCystic fibrosis (CF) is a monogenic disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, which encodes a Cl−/HCO3− ion channel located at the apical plasma membrane (PM) of epithelial cells. CFTR dysfunction disrupts epithelial barrier integrity, drives progressive airway remodelling and has been associated with epithelial-to-mesenchymal transition (EMT), a process in which cells lose epithelial properties and acquire mesenchymal characteristics. We previously demonstrated that mutant CFTR directly drives partial EMT, independently of secondary events such as bacterial infection or inflammation. MethodsHere, we investigated whether PM localisation of CFTR alone is sufficient to preserve epithelial integrity or if its ion transport function is also required using polarized CF bronchial epithelial (CFBE) cells expressing wt-, p.Phe508del-, or p.Gly551Asp-CFTR. While p.Phe508del-CFTR is retained in the endoplasmic reticulum (ER) and fails to traffic to the PM, p.Gly551Asp-CFTR reaches the PM but lacks ion transport function. To this end we assessed transepithelial electrical resistance (TEER), cell proliferation, wound healing, and expression of epithelial and mesenchymal markers by Western blot and immunofluorescence.ResultsThe degree of mesenchymal phenotype was higher in cells expressing p.Phe508del-CFTR vs. those expressing PM localized but non-functional p.Gly551Asp-CFTR. This was evidenced by lower TEER, higher expression of mesenchymal markers (N-cadherin, vimentin), and lower E-/N-cadherin ratio. Furthermore, both CF cells displayed delayed wound healing compared to wt-CFTR cells, while only p.Phe508del-CFTR cells, but not p.Gly551Asp-CFTR cells, showed increased cell proliferation. Moreover, treatment with CFTR modulators (CFTRm) partially restored tight junction integrity by increasing claudin-1 levels and E-/N-cadherin ratio in both mutant cells. TGF-β1 treatment induced EMT in all three cell lines by decreasing epithelial markers (E-cadherin, cytokeratin 18, claudin-1) while increasing N-cadherin levels. However, mesenchymal marker vimentin increased only in CF cells, and more prominently in p.Phe508del-CFTR than in p.Gly551Asp-CFTR cells. Additionally, CFTR inhibition in wt-CFTR cells, partially mimicked p.Gly551Asp-CFTR behaviour, i.e., reduced claudin-1 levels.DiscussionAltogether, these findings demonstrate that the loss of CFTR ion transport, despite the physical presence of (nonfunctional) CFTR at the PM, is enough to trigger partial EMT. However, the severity of the EMT phenotype worsens when CFTR is absent from the PM while also increasing susceptibility to TGF-β1-triggered EMT. Moreover, CFTRm only partially reverse this CF EMT state, indicating that full epithelial integrity will likely require targeting additional factors.